2018
DOI: 10.1088/1361-648x/aabcff
|View full text |Cite
|
Sign up to set email alerts
|

Ab initiostudy for the IR spectroscopy of PbTiO3and PbZrO3, primary blocks of PbZr1−xTixO3

Abstract: PbTiO (PT) and PbZrO (PZ) are the two primary blocks of the solid solution PbZr Ti O (PZT). They can be modelled in different ways; but, in order to do comparable DFT calculations on PZT, with different values of x, one must find a unique method that can be used for both PT and PZ. In particular, we want to evaluate their vibrational properties to compare them with experimental data. Density functional theory (DFT) is used to perform structure geometry optimizations and electronic structure calculations, both … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 51 publications
0
8
0
Order By: Relevance
“…In a previous study, some of us developed a model for the two pure compounds, PT and PZ, within the framework of Density Functional Theory (DFT). 17 We showed that the SOGGA functional 18 is a reliable choice for describing these materials' properties. Here, we use this functional for calculating the IR absorption spectra of pure PT and PZ, as well as PZT of various compositions (x ≥ 0.5) in both the cubic and tetragonal phases.…”
Section: ■ Introductionmentioning
confidence: 95%
See 4 more Smart Citations
“…In a previous study, some of us developed a model for the two pure compounds, PT and PZ, within the framework of Density Functional Theory (DFT). 17 We showed that the SOGGA functional 18 is a reliable choice for describing these materials' properties. Here, we use this functional for calculating the IR absorption spectra of pure PT and PZ, as well as PZT of various compositions (x ≥ 0.5) in both the cubic and tetragonal phases.…”
Section: ■ Introductionmentioning
confidence: 95%
“…Calculated Infrared and THz Spectra of PZ (PbZrO 3 ) and PT (PbTiO 3 ). In a previous article, 17 we highlighted the need to carry out precise modeling to interpret the IR spectra of perovskites such as PT and PZ. The use of the SOGGA functional, 18 implemented in the 2014 version of the CRYSTAL computer code, 30 permitted the determination of a good description of the structural and electronic structure of the two compounds.…”
Section: ■ Introductionmentioning
confidence: 99%
See 3 more Smart Citations